Construction and validation of a detailed kinetic model of glycolysis in asexual Plasmodium falciparum : a feasibility study - Penkler, Gerald Patrick (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MSc (Biochemistry))--University of Stellenbosch, 2009.